(untitled) (Journal of the College of Basic Education, 2026)
This research aims to identify the effectiveness of a proposed strategy based on cognitive representation models in the achievement of Arabic grammar among fourth-grade literary students. To achieve the research objective, the researcher selected a sample of (72) female students from the fourth-grade literary students at Umm Al-Mu’minin Secondary School for Girls affiliated with the General Directorate of Education in Al-Rusafa II. They were randomly distributed into two groups, with (37) female students in the experimental group and (35) female students in the control group. The researcher rewarded the students of the two research groups on seven variables: (chronological age calculated in months, fathers’ academic achievement, mothers’ academic achievement, pre-test scores for higher-order thinking, pre-test scores for achievement, academic motivation scale scores, and intelligence test scores). After identifying the scientific material that included (10) Arabic grammar topics to be taught to fourth-grade literary students, the researcher formulated (191) behavioral objectives for the topics, and prepared model lessons for each of the topics specified for the experiment. To measure the achievement of the students of the two research groups in the ten topics, the researcher prepared an objective achievement test consisting of (40) multiple-choice items, and verified its validity and reliability. Using a two-sample t-test for independent samples to process the data, a statistically significant difference at the significance level of 0.05 was found between the achievement of the students in the two research groups, in favor of the students in the experimental group, who were taught using a strategy based on cognitive representation models. In light of the research results, the researcher drew several conclusions, including: The use of the proposed strategy based on cognitive representation models led to positive student interaction with Arabic grammar lessons. This was evident in their active participation throughout the experiment. Students expressed their desire to engage in the subject-related activities, which provided them with positive learning approaches. The researcher recommended the use of cognitive representation models in teaching Arabic grammar, and suggested conducting several additional studies to complement this study.